Uniform Crime Reports: National Time-Series Community-Level Database, 1967-1980 - Pierce, Glenn L. ([Verlag nicht ermittelbar], 1984)
The Uniform Crime Reports National Time-Series Data, 1967-1980, include detailed criminal offense and clearance information submitted monthly by over 3,000 consistently reporting law enforcement agencies in the United States. These data, provided in annually pooled cross-sections, were processed at the Center for Applied Social Research, Northeastern University, Boston, Massachusetts to produce easily accessible and highly reliable time-series data on officially reported crime. Originally provided by the Federal Bureau of Investigation (FBI), these data exclude Uniform Crime Report (UCR) data from infrequently reporting law enforcement agencies. In general, only those agencies that submitted ten or more monthly reports in every year during 1967 through 1980 are included in this collection. The data include detailed breakdowns of offenses and clearances taken from disaggregated UCR Return A tapes. Of particular interest are weapon-specific robbery and assault variables, types of rape, burglary, larceny, and motor vehicle theft, and clearances by arrest (or other exceptional means) of adults and juveniles for each offense sub-type. Both monthly and annual counts of these are available. Finally, as an aid to the user, each agency is identified by its FBI "ORI Code" as well as a sequential case number produced and documented by ICPSR in the codebook's appendix. Cases also may be identified by geographic region, state, SMSA, county, population size and group, and frequency of reporting.